Total ozone potential vorticity and tropopause pressure : A comparative Analysis over south-east Asia - BEGUM, D. A. (MAUSAM, 2001)
On the basis of TOMS data, a comparative analysis of total ozone. potential vorticity and tropopause pressure has been done over the area 20°- 50° N, 90° -160° E (south-east Asia) for a period October 1982 to September, 1983. The study has been done for three different latitude bands 20°-30° N, 30°-40° N and 400-50° N. High correlations have been found near the tropopause level at all seasons except in autumn.